Peran Kepemimpinan dalam Transformasi Birokrasi: Studi Kasus Pemimpin yang Sukses Mendorong Perubahan - Ovilla Dwi Qoirunnisa; Hayat Hayat; Suyeno Suyeno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research highlights how leaders act as agents of change, planning, organizing, and mobilizing resources to achieve effective change. This research strategy uses a phenomenological method with a qualitative approach. This research also refers to the literature review method as the primary approach. Literature reviews aim to solve problems through in-depth and critical analysis of relevant library sources. The library analysis process involves techniques for collecting information data from various library references that are considered important sources of ideas. This research shows successful change leaders can create an environment where people feel motivated to change, work together, and innovate. The role of leadership is very important to success in managing organizational change. Leadership that is adaptive, innovative, and able to lead through uncertainty will lead organizations toward a more resilient future. Conclusion Change leaders must have strategic intelligence, interpersonal skills, and a deep understanding of organizational dynamics. Effective leadership paves the way for sustainable organizational change and achieving goals. Keywords: Bureaucracy Leadership, Role, Transformation